Encapsulation of entomopathogenic nematodes in polymer-based materials and their effect on Galleria mellonella - Bogantes, Delia (2018)
The entomopathogenic nematodes (EPN) Heterorhabditis are used for the biological control of insect pests, most of the applications of these organisms involve the use of abundant water and do not involve protection against unfavorable environmental conditions; for this reason, there is a need to develop formulations that facilitate the application and extend the life span of these organisms. Encapsulating nematodes in hydrogels or capsules is a promising alternative to increase the viability of Heterorhabditis sp. Twentythree different formulations from biopolymers pectin, carboxymethylcellulose (CMC), alginate and gelatin were evaluated; 15 of these formed capsules. Hydrogels prepared from 2.0% alginate, 4.2% pectin and 2.2% CMC were chosen since they presented the best conditions regarding shape, ability to retain nematodes and consistency. Alginate was chosen from these materials because of its characteristics of viability of the nematodes and absence of contamination. The retention and viability of infective juveniles (JI) were evaluated at 2%, 3% and 4% alginate concentrations, with alginate capsules at 2% showing the best results. When the ability of these capsules to infect larvae of Galleria mellonella was determined, it was found that an increase in the concentration (JI. ml-1) and the dose (Capsules.larva-1) caused an increase in the percentage of infection. Finally, it was determined that the LD50% corresponded to 2.9 capsules.larva-1.